한국형 출혈열 VIII . 한국형 출혈열 병원체 한탄바이러스의 중화항체에 관한 연구 - 이호왕; 백락주; 박덕수 (Journal of bacteriology and virology, 1982)
Korean hemorrhagic fever (KHF) was recognized for the first time in Korea in 1951 during Korean War among United Nations troops although similar diseases to KHF had been reported as bemorrhagic nephroso-nephritis in Russia, as epidemic hemorrhagic fever in China, as nephropathia epidemica in Scandinavia and epidemic hemorrhagic fever in Eastern Europe and in Japan. In recent years it appears to have spread slowly in a southwesterly direction and about 800 hospitalized cases are clinically diagnosed each year in Korea. Recently, Lee et al discovered the etiologic agent of KHF, Hantaan virus, and animal reservoir host of KHF and perfected serologic test for diagnosis of the disease but there is no report on neutralizing antibodies of KHF to date. This is the first report on neutralizing antibody in the sera of KHF patients and of immunized rabbit with Hantaan virus. 1. It was demonstrared that infectivity of Hantaan virus was neutralized with serum antibodies of KHF patients in Apodemus mice. 2. Neutralizing antibody was appeared on 7th days after onset of illness and it was remained for 10 years at least. 3. Neutralizing antibody appeared more quickly and higher than immunofluorescent antibody in the patients. 4. Immunafluorescent antibody and neutralizing antibody were produced in rabbits after inoculation of the virus intramuscularly